ANALISIS FISIKO-KIMIA ES KRIM DENGAN PENAMBAHAN JAGUNG MANIS (ZEA MAYS L. SACCHARATA) DAN RUMPUT LAUT (EUCHEUMA COTTONII) - Satriani, Satriani; Sukainah, Andi; Mustarin, Amirah (Universitas Negeri Makassar, 2018)
The purpose of this research to know the effect of additions of sweet corn porridge and seaweed porridge against physical and chemical characteristics of ice cream, as well as to know the best concentration on the addition of sweet corn porridge and seaweed porridge.This research is an experiment research with a factorial completely randomized design consisting of two factors, factor A is the sweet corn porridge (0%, 3%, 9% and 15%) and the B factor is seaweed porridge (0%, 0.3%, 0.5% and 0.7%) which done with 10 thetreatments and 3 time repetitions. The research variables observed were overrun, speed melt, fat content, protein content, carbohydrate content, and organoleptic test include color, taste, aroma and teksture. The analytical technique used in this study is the analysis of variance analyzed using SPSS version 22.0. The results showed the best treatment is the additions of sweet corn porridge 15% and seaweed porridge 0.7% with the best quality indicators based on the overrun test parameter (1.11%) ,speeds melt (59.85 minute), fat content (2.13%), protein content (3.72%), carbohydrate content (36.09%), and organoleptic tests include: color (4.21%), taste (4.20%), aroma (4.12%) and teksture (4.24%)